PROFIL LITERASI SAINS SISWA SD DALAM PROGRAM KAMPUS MENGAJAR ANGKATAN 8 - Rika Widya Sukmana; Deasy Rahmawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Literacy skills are important for students to have in facing the development of 21stcentury. This is quite fundamental in order to be able to solve problems amidstincreasingly complex issues. This study aims to describe the profile of scienceliteracy skills of students in Bandung Regency and Bandung City which schoolsreceived the Kampus Mengajar (KM) Program batch 8. The research method usedis a descriptive survey method. Research samples were 66 elementary schoolstudents spread across three schools in Bandung Regency and the City. Data onstudents' science literacy skills were collected through written tests on theDigestive System. The collected data were then analyzed descriptively using theSPSS version 23 for Windows program. The results obtained in this study indicatethat the science literacy skills of elementary school students in the BandungRegency and the City areas have quite significant differences. In Bandung city, thescience literacy profile reviewed from 3 aspects is in the medium to high category.While in the Bandung Regency area, the science literacy profile of elementaryschool students is included in the low category. In general, it can be said that thescience literacy profile of elementary school students in the Campus TeachingProgram Batch 8 is in the